Prevalence and influencing factors of osteoporosis in Yugur adult women in Gansu province: a cross-sectional survey - Xiao-lan REN; Ming-yang LI; JI-hong HU (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo explore the prevalence and influencing factors of osteoporosis and to analyze the relationship between biochemical indicators and bone mineral density among Yugur menopausal women and adult women (aged 20 - 80 years) in Gansu province.MethodsUsing stratified cluster sampling, we recruited 960 Yugur female residents aged 20 - 80 years in Su'nan Yugu Autonomous County, Gansu province and conducted a questionnaire survey, laboratory test and physical examination including calcaneal bone mineral density detection in the women during July - August 2016. Multivariate logistic regression was used to analyze associates of osteoporosis prevalence and multivariate linear regression was adopted to assess the relationship between biochemical indicators and bone density.ResultsFor the 929 participants with complete information, the crude and standardized prevalence rate of osteoporosis was 27.64% and 23.53% and those were 13.99% and 12.78% for the menopausal participants, respectively. The prevalence rate of osteoporosis increased significantly with age among all the participants (χ2 = 114.576) and the menopausal participants (χ2 = 31.664) (both P < 0.05). The results of logistic regression analysis revealed that for menopausal women, the influencing factors of osteoporosis prevalence included marital status, menopause duration, and grip strength; while for adult women, the influencing factors included age, education, fracture history, and grip strength. Alkaline phosphatase was reversely correlated with bone mineral density significantly in menopausal women (β = - 0.003) and in the women aged 20 - 80 years (β = - 0.004) (both P < 0.05).ConclusionAmong Yugur menopausal women and 20 - 80 years old women in Gansu province, the prevalence rate of osteoporosis is relatively low and increases with age; the main risk factors of osteoporosis prevalence include age, duration of menopause and fracture history; alkaline phosphatase is a predictor for bone density reduction in the women.